Pengaruh Adopsi Teknologi dan Modal Terhadap Produktivitas Petani Padi di Desa Sekumpul, Kecamatan Sawan, Kabupaten Buleleng - Luh Ely Supriantini; I Wayan Suwendra (Jurnal Pendidikan Ekonomi Undiksha, 2026)
This study aims to analyze the influence of technology adoption and capital on rice farmer productivity. Rice farmer productivity fluctuates from year to year, necessitating an examination of the influencing factors. This study employed a quantitative approach with a causal design. The population in this study was all rice farmers. The research sample was determined using a probability sampling technique with a random sampling approach, so that all farmers became respondents. Data were collected through questionnaires and documentation. Data analysis was conducted using multiple linear regression after meeting the classical assumption test. The results showed that technology adoption had a positive and significant effect on rice farmer productivity. Capital also had a positive and significant effect on rice farmer productivity. Simultaneously, technology adoption and capital significantly influenced rice farmer productivity. This study concluded that increasing rice farmer productivity depends on farmers' ability to adopt agricultural technology and the availability of adequate business capital..